The effect of continuing education of neonatal intensive care nursing on knowledge and the practice of the nurses working in the children's hospitals - Goudarzi; Z. Tefagh; M. Monjamed; Z. Memari; A. Kamali; P (Tehran University of Medical Sciences, 2004)
Introduction: Nowadays continuing education is considered an essential part of nursing education. This study was planned to evaluate the effect of continuing education of neonatal intensive care nursing on knowledge and the practice of nurses who were working in the children's hospitals. Materials and Methods: A semi-experimental study was carried out including 42 nurses of the children's hospitals affiliated to Tehran University of Medical Sciences during 18 months in 1999- 2000. The data were collected by a questionnaire and a checklist. The questionnaire included demographic information and 60 multichoices questions based on the knowledge of the neonatal intensive care nursing. The observation checklist contained 5 parts, how to establish: resuscitation operation, endotracheal suction, management of the patient under mechanical ventilation, nasogastric tube insertion and feeding by gavage. At the end of the training courses the questionnaire and the checklist were completed again individually. The result of the pre and post tests and checklist were compared in the areas of knowledge and practice. The data was analyzed by 2 and paired t Student test. Results: Statistical analysis showed a meaningful difference in the knowledge and practice after the continuing nursing education (p<00001). Conclusion: This research revealed the positive effect of the continuing nursing education on the knowledge and the practice of the nurses who were working in the pediatric wards. It is important to consider the continuing nursing education program to promote the health care system.